2005
DOI: 10.1021/es049731f
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Household Concentrations of Multiple Indoor Air Pollutants in China

Abstract: Most previous studies on indoor air pollution from household use of solid fuels have used either indirect proxies for human exposure or measurements of individual pollutants at a single point, as indicators of (exposure to) the mixture of pollutants in solid fuel smoke. A heterogeneous relationship among pollutant-location pairs should be expected because specific fuel-stove technology and combustion and dispersion conditions such as temperature, moisture, and air flow are likely to affect the emissions and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
6

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 17 publications
(33 reference statements)
4
35
6
Order By: Relevance
“…In winter, the highest PM 2.5 (368.5 μg m −3 ) and PM 10 (588.7 μg m −3 ) were recorded in sitting rooms. This indicated that heating practice is a prominent determinant of indoor air quality in rural Henan, similar to other studies conducted in other rural areas (Inner Mongolia, Gansu, Shaanxi, and Guzhou) of China (Fischer and Koshland, 2007;He et al, 2005;Jin et al, 2005). In Baofeng, the outdoor PM 10 concentrations in winter were not as low as expected and even higher than in kitchens and sitting rooms, which might be due to the coal mine activities close to the village.…”
Section: Discussionsupporting
confidence: 86%
“…In winter, the highest PM 2.5 (368.5 μg m −3 ) and PM 10 (588.7 μg m −3 ) were recorded in sitting rooms. This indicated that heating practice is a prominent determinant of indoor air quality in rural Henan, similar to other studies conducted in other rural areas (Inner Mongolia, Gansu, Shaanxi, and Guzhou) of China (Fischer and Koshland, 2007;He et al, 2005;Jin et al, 2005). In Baofeng, the outdoor PM 10 concentrations in winter were not as low as expected and even higher than in kitchens and sitting rooms, which might be due to the coal mine activities close to the village.…”
Section: Discussionsupporting
confidence: 86%
“…i All numbers given as a proportion (percent) of all stoves of the specified type. (17) in four homes in a single village. This difference is partly because the pilot measurements were intended for selecting appropriate sampling points and pollutants for the larger study, rather than being from a representative sample households.…”
Section: Measurement Locations and Timesmentioning
confidence: 99%
“…There are many emitting sources for PAHs in indoor environment including the smoking, cooking, and domestic fuel combustion (He et al 2005;Riechelmann et al 2007). PAHs in outdoor environment can be derived from the vehicle emission, power generation by coal combustion, petroleum refining, and waste burning (Peng et al 2011).…”
Section: Introductionmentioning
confidence: 99%